Analisis Kesehatan dan Keselamatan Kerja Menggunakan Metode Job Safety Analysis (JSA) di Café +62 Coffee Meals - Luthfi Alfian Arsyid; Asep Erik Nugraha (Jurnal Ilmiah Wahana Pendidikan, 2022)
K3 is an effort and thought to ensure the integrity and perfection of both physical and spiritual people in general and labor in particular, along with the results of his work towards a just and prosperous society. As the coffe industry grows, coffee enthusiasts are increasing and coffee shops / cafés are mushrooming in every region. This leads to increasingly tight competition in the coffee industry, the facilities used to make coffee are still quite simple, employees stand in front of a table that is too short so that when employees make coffee must bend and look towards the workpiece. The purpose of this study is to analyze the potential hazards that can occur and minimize accidents at work using the Job Safety Analysis method. The benefits of research is knowing what are the potential dangers that occur and provide solutions to problems that occur